2017
DOI: 10.1002/jcb.25724
|View full text |Cite
|
Sign up to set email alerts
|

Does the Harvesting Technique Affect the Properties of Adipose‐Derived Stem Cells?—The Comparative Biological Characterization

Abstract: The objective of this study was to evaluate complex biological properties of human stem cells isolated from adipose tissue (ASCs) harvested utilizing different methods: surgical resection (R), power-assisted liposuction (PAL), and laser-assisted liposuction (LAL). ASCs were isolated from healthy donors, due to surgical resection, power-, and laser-assisted liposuction. Isolated cells were characterized by their clonogenicity, proliferation rate, doubling time, multilineage differentiation, and senescence poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 51 publications
0
35
0
5
Order By: Relevance
“…Earlier studies reported the heterogeneity in SVF and great variability in the percentages of different subsets [ 35 , 36 ]. Some reports have focused mostly on the difference in the isolation methods, handling, variability of cell yields and mode of administration [ 37 , 38 ]. To date, there are insufficient data to establish a correlation between SVF-dose, and direct therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies reported the heterogeneity in SVF and great variability in the percentages of different subsets [ 35 , 36 ]. Some reports have focused mostly on the difference in the isolation methods, handling, variability of cell yields and mode of administration [ 37 , 38 ]. To date, there are insufficient data to establish a correlation between SVF-dose, and direct therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The content of preadipocytes is less in the primary ADSCs 'mix' (23,25,26) and preadipocytes share several cell markers with the primary adipose derived stem cells, like Lin -, CD29 + , CD34 + , Sca-1 + , and CD45 -CD31 - (23,25), making it difficult to screen for preadipocytes alone from the primary ADSC 'mix' using fluorescence-activated cell sorting. In the clinical practice of regenerative medicine, generally, the ADSCs was used and observed as a whole (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Culturing with increasing cell passages was found to reduce the heterogeneity of ADSCs (11). Studies indicated that continuous cell passages reduced the number of cells with a CD34 + surface marker, which differentiated into adipocytes more efficiently (25,27). However, whether spontaneous adipogenic differentiation of ADSCs would decrease with serial cell passages is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation capacity into the adipogenic, osteogenic, and chondrogenic lineage was performed as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stem cells were additionally analyzed for the presence of the specific surface markers CD34, CD44, CD45, and CD90 by flow cytometry according to the protocol previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%